An Exploration of the Readiness, Challenges and Expected Support for Their Overseas Study of Chinese Business and Management Programme Students. (19th August 2015) - Wang, Chengbo; Li, Xiaomei; Ou, Xuan; O'Kane, James; Mao, Zhaofang; Zhang, Wenquan
Abstract Chinese students are the largest international student cohort in the higher education institutions of English‐speaking developed countries. The paper explores strategies to enhance the Chinese students' learning efficacy in overseas institutions. This research differs from other research focusing on international students already in English‐speaking institutions; it explores the readiness of potential Chinese international students before departure from China, their anticipated challenges for study abroad and expected support from host institutions and staff. Besides the insights of anticipated challenges and expected support, the key findings include: the majority of the sample students are financially ready for overseas study, however they are not fully ready on English language; students from the public institute in the study have a higher level of readiness for subject knowledge than their private institute's peers. The findings offer a guide, to both the English‐speaking institutions and their Chinese partners, on facilitating, teaching and preparing the Chinese students for a fruitful learning experience abroad and enhanced academic performance.